Efficient Knockdown and Lack of Passenger Strand Activity by Dicer-Independent shRNAs Expressed from Pol II-Driven MicroRNA Scaffolds - Erik Kaadt; Sidsel Alsing; Claudia R. Cecchi; Christian Kroun Damgaard; Thomas J. Corydon; Lars Aagaard (Elsevier, 2019)
The expression of short hairpin RNAs (shRNAs) may result in unwanted activity from the co-processed passenger strand. Recent studies have shown that shortening the stem of conventional shRNAs abolishes passenger strand release. These Dicer-independent shRNAs, expressed from RNA polymerase III (Pol III) promoters, rely on Ago2 processing in resemblance to miR-451. Using strand-specific reporters, we tested two designs, and our results support the loss of passenger strand activity. We demonstrate that artificial primary microRNA (pri-miRNA) transcripts, expressed from Pol II promoters, can potently silence a gene of choice. Among six different scaffolds tested, miR-324 and miR-451 were readily re-targeted to direct efficient knockdown from either a CMV or a U1 snRNA promoter. Importantly, the miR-shRNAs have no passenger strand activity and remain active in Dicer-knockout cells. Our vectors are straightforward to design, as we replace the pre-miR-324 or -451 sequences with a Dicer-independent shRNA mimicking miR-451 with unpaired A-C nucleotides at the base. The use of Pol II promoters allows for controlled expression, while the inclusion of pri-miRNA sequences likely requires Drosha processing and, as such, mimics microRNA biogenesis. Since this improved and tunable system bypasses the requirement for Dicer activity and abolishes passenger strand activity completely, it will likely prove favorable in both research and therapeutic applications in terms of versatility and enhanced safety. Keywords: RNAi, Dicer-independent shRNA, miR-451, miR-324, agoshRNA, agshRNA, passenger strand activity, Drosha, U1 promoter, Pol-II driven miRNA scaffold